DENTAL MANAGEMENT OF ORAL COMPLICATIONS IN PATIENTS UNDERGOING ONCOLOGY TREATMENT (REMUNOM, 2024)
Cancer, resulting from mutations in cellular DNA, triggersuncontrolled cellular activity. Specific genes, normally inactive,can undergo changes, contributing to oncogenesis. Oncologydentistry is crucial for patients’ quality of life during treatment. This article highlights possible oral complications duringtherapy and reviews the importance of oncological dentistry inpreventing and managing these complications, aiming to improve quality of life and therapeutic outcome. Radiation causes structural and functional damage and cell loss in normalcells, leading to varied injuries depending on several factors.Oncological dentistry plays a crucial role in the prevention andmanagement of emerging oral complications. Beforeantineoplastic treatment, a complete dental evaluation isessential to treat pre- existing conditions that may increase therisk of complications. Preventative measures include oralhygiene instructions, complete prophylaxis, and use of topicalagents to stimulate salivation. In addition, specific treatments arecarried out, such as cavity removal and restorations, endodontictreatment, tooth extractions and periodontal care. Aninterdisciplinary approach, involving oncologists, dentists and other healthcare professionals, is essential to guarantee the oralhealth and well-being of patients during treatment. Byrecognizing the importance of oncological dentistry andimplementing appropriate measures, it is possible tosignificantly improve the quality of life and prognosis of cancerpatients.